2001
DOI: 10.1177/1358836x0100600207
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter embolization of renal artery aneurysm in Behçet’s disease

Abstract: A 20-year-old man with Behçet's disease presented with a ruptured renal artery aneurysm. This patient had previously had aneurysms of the coronary arteries and coronary vein thrombosis that were treated with immunosuppression. A selective transcatheter embolization of the renal artery branch was done successfully and treatment with corticosteroids and methotrexate was added. Presented here is a rare complication of Behçet's disease, with discussion on the pathophysiology, differential diagnosis, and the advant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Murakami et al [2] reported that they investigated 97 cases of vasculo-Behçet's disease and found no patient who developed abnormalities in the small renal, celiac or superior mesenteric arteries. To the best of our knowledge, at least six cases of vasculo-Behçet's disease, including our case, have been reported with the complication of renal artery abnormalities [3][4][5][6][7]. Moreover, including our case, only five cases of vasculo-Behçet's disease have been reported to be complicated with abnormalities in the celiac and superior mesenteric arteries [4,[8][9][10].…”
Section: Discussionmentioning
confidence: 78%
“…Murakami et al [2] reported that they investigated 97 cases of vasculo-Behçet's disease and found no patient who developed abnormalities in the small renal, celiac or superior mesenteric arteries. To the best of our knowledge, at least six cases of vasculo-Behçet's disease, including our case, have been reported with the complication of renal artery abnormalities [3][4][5][6][7]. Moreover, including our case, only five cases of vasculo-Behçet's disease have been reported to be complicated with abnormalities in the celiac and superior mesenteric arteries [4,[8][9][10].…”
Section: Discussionmentioning
confidence: 78%
“…Etiologies for secondary renal artery aneurysms include pregnancy, trauma, iatrogenic causes, congenital malformations of the kidneys, malignancies, mycotic infections, neurofibromatosis, tuberous sclerosis, Ehlers-Danlos syndrome, and connective tissue diseases such as polyarteritis nodosa, Wegener's granulomatosis, and Behcet's disease. 4,6,11,12 The classic presentation for renal artery aneurysm prior to rupture consists of microscopic hematuria, hypertension, and flank and/or abdominal pain. Patients may also present with spontaneous rupture, or findings of an abdominal bruit or mass on examination.…”
Section: Discussionmentioning
confidence: 99%
“…Coil embolization has been used to treat ruptures. 36,37 Limited experience with PTA to treat symptomatic stenoses resulting in hypertension or azotemia suggests it may be useful in carefully selected patients. 38 Renal vein thrombosis (RVT), which occurs in up to 10% of those with nephrotic syndrome, may also be seen in association with Behçet's disease and SLE, and present with hematuria.…”
Section: Discussionmentioning
confidence: 99%